Implementasi Metode TOPSIS Dalam Sistem Pendukung Keputusan Penilaian Kinerja Guru Honor - Selvira, Rani; Tinambunan, Miko Putra Haposan; Bu'ulolo, Efori (ADA Journal of Information System Research, 2024)
This research aims to implement the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method in the Decision Support System (SPK) for honorary teacher performance assessment. Problems in assessing the performance of honorary teachers are the main focus of this research. The aim is to create a more objective and structured SPK, which is able to provide a more accurate assessment of the performance of honorary teachers. In this research, honorary teacher performance data was collected from various sources, such as observation results, assessments from school principals, and evaluations from colleagues. The data is then processed using the TOPSIS method to give weight to each assessment criterion, which includes aspects of knowledge, teaching skills, discipline and the teacher's contribution to student progress. The research results show that the implementation of the TOPSIS method in the SPK for honorary teacher performance assessment has been successful. The developed SPK can provide more objective and consistent recommendations in assessing the performance of honorary teachers. This helps school principals and other authorities in making decisions regarding promotions, awards or training required by honorary teachers. By using the TOPSIS method, the performance assessment of honorary teachers becomes more structured and objective. This has the potential to increase transparency and accountability in the honorary teacher performance assessment process. The results of this research provide an important contribution to the development of a better performance assessment system for honorary teachers, which will ultimately have a positive impact on the quality of education at various levels. The results obtained were obtained by A1 with a value of 0.9038 as the highest value.